Radical Trachelectomy Performed During Pregnancy: A Review of the Literature. Issue 4 (May 2016) - Căpîlna, Mihai Emil; Szabo, Belá; Becsi, Janos; Ioanid, Nicolae; Moldovan, Bogdan
Abstract : Objective: Cervical cancer is one of the most frequent malignant diseases diagnosed during pregnancy. Abdominal or vaginal radical trachelectomies are fertility-preserving alternatives to radical hysterectomy for young women with early-stage cervical cancer that can be performed during ongoing pregnancy. Methods: A literature review of articles on this subject was conducted through a Medline search for articles published in English or French. Results: At this moment, 21 cervical cancer patients, including ours (4 stage IA2, 16 IB1, and 1 IB2) who underwent radical trachelectomy during pregnancy have been reported. Of these, 10 were performed by vaginal route and 11 were abdominal radical trachelectomies. Conclusions: Radical trachelectomy could be offered as an option for pregnant patients with early invasive cervical cancer. It may help women avoid the triple losses of a desired pregnancy, fertility, and motherhood.